Measuring Waqf Performance: A Comprehensive Analysis of the 2024 National Waqf Index - Nurul Huda; Ariel Nian Gani; Muhammad Rofi'i; Nova Rini; Ridzwan Bakar; Sulistyowati Sulistyowati; Emmy Hamidiyah; Shalahuddin Ahmad; Tatang Astaruddin; Arief Rohman Yulianto; Nurkaib Nurkaib; Nani Almuin (Talaa : Journal of Islamic Finance, 2026)
Waqf plays a strategic role in building social welfare and supporting national development, but its management in Indonesia still faces challenges of disparity between regions. The National Waqf Index (IWN) serves as a quantitative instrument to systematically and objectively measure the performance of the waqf ecosystem in 34 Indonesian provinces. This study examines the 2024 IWN based on six main pillars: regulations, institutions, processes, systems, outcomes, and impacts, using the Multi-stage Weighted Index method and primary and secondary data from various official sources. The results indicate that the greatest strength of national waqf lies in the regulatory and institutional aspects, with provinces such as Riau, Aceh, and West Kalimantan standing out. However, the process and outcome aspects show the lowest scores nationally, indicating a gap between structural readiness and implementation effectiveness. These findings emphasize the need for human resource capacity building, digital transformation, cross-sectoral approaches, and affirmative interventions in disadvantaged regions to ensure the significant contribution of waqf to sustainable development goals.